The Influence of Brand Image and Brand Awareness on the Decision to Purchase an iPhone in Cirebon - Fardan Walidina; Lis Tatin Hernidatiatin (Indonesian Journal Economic Review (IJER), 2026)
This study examines the influence of brand image and brand awareness on the decision to purchase an iPhone in the city of Cirebon. The issue addressed is the shift in consumer behavior, where consumers no longer consider price alone but also psychological factors such as brand image and brand awareness when making purchasing decisions. The objective of this study is to determine the influence of brand image and brand awareness, both individually and collectively, on purchasing decisions. The method used is a quantitative approach with an explanatory research design, employing data collection via a questionnaire administered to 394 iPhone users, and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that brand image and brand awareness significantly influence purchasing decisions, both partially and simultaneously, with an R-square value of 62.2%, indicating a strong influence. The implications of this study highlight the importance for companies to enhance brand image and brand awareness through effective marketing strategies to drive consumer purchasing decisions, particularly in the premium smartphone market in the Cirebon region.